A primer on sustainability : in the business environment - Whitfield, Ronald. (2014 digital library., 2014)
What does sustainability in the business environment really mean? The concept has evolved from a vague goal to "save the planet" to become a strategic imperative for business to enhance performance across many dimensions. We live in an age of increasing corporate accountability and if a business expects to survive for the long term, it must adhere to ever higher standards of behavior and continuously develop more sustainable ways of doing business.